I take you : a novel - Kennedy, Eliza, 1974- (Crown Publishers, 2015)
"Lily's fiancé Will is a brilliant, handsome archaeologist. Lily is sassy, impulsive, fond of a good drink (or five) and has no business getting married. Lily likes Will, but does she love him? Will loves Lily, but does he know her? As the wedding approaches, Lily's nights--and mornings, and afternoons--of booze, laughter, and questionable decisions become a growing reminder that the happiest day of her life might turn out to be her worst mistake yet"--Amazon.com.